Insulin-Like Growth Factor-I and Progesterone Release by Ovarian Granulosa Cells of Hens after Experimental Lead and Molybdenum Administrations in vitro - Kolesarova, Adriana; Capcarova, M.; Sirotkin, A.; Massanyi, P. (International Journal of Poultry Science, 2009)
The general objective of this in vitro study was to examine the secretory activity of ovarian granulosa cells of hens after lead (Pb) and molybdenum (Mo) administrations. In this study the effect of various doses of Pb and Mo on the insulin-like growth factor-I (IGF-I) and progesterone (P4) release by ovarian granulosa cells was demonstrated. Ovarian granulosa cells were incubated with lead acetate/ammonium molybdate- group A 0.09 mg/mL, group B 0.17 mg/mL, group C 0.33 mg/mL and the control group without Pb and Mo administrations for 18 h. The IGF-I and progesterone release by granulosa cells of hens was assessed by RIA. It was demonstrated that isolated ovarian cells were able to survive in culture and release hormones IGF-I and P4 after experimental Pb and Mo administrations. Our observations demonstrated that the secretory activities of granulosa cells of hens were dependent on Pb and Mo doses. Lower Pb concentrations (0.09 mg/mL and 0.17 mg/mL) induced IGF-I release but higher dose (0.33 mg/mL) stimulated P4 release by ovarian granulosa cells of hens. Higher Mo concentration (0.33 mg/mL) reduced of IGF-I release while doses 0.17 mg/mL and 0.33 mg/mL stimulated P4 release by ovarian cells of hens. These findings contribute to our knowledge of the effect of lead and molybdenum on ovarian function of hens.